2017
DOI: 10.1177/1362361316683889
|View full text |Cite
|
Sign up to set email alerts
|

The levels of physical activity and motor skills in young children with and without autism spectrum disorder, aged 2–5 years

Abstract: Autism spectrum disorder is the fastest growing developmental disability in the United States. As such, there is an unprecedented need for research examining factors contributing to the health disparities in this population. This research suggests a relationship between the levels of physical activity and health outcomes. In fact, excessive sedentary behavior during early childhood is associated with a number of negative health outcomes. A total of 53 children participated in this study, including typically de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 44 publications
0
33
2
1
Order By: Relevance
“…For instance, children with ASD had similar PA levels as TD children based on accelerometer data; however, parent reports indicated that children with ASD had lower levels of PA and participated in a narrower range of activities than the TD children (Bandini et al, 2013). Further, Ketcheson et al (2018) found that preschoolers with ASD were less sedentary than TD children, while Pan et al (2011) found the opposite. However, there is encouraging evidence overall suggesting that people with ASD are at least capable of reaching the physical activity guidelines for TD individuals (Tyler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, children with ASD had similar PA levels as TD children based on accelerometer data; however, parent reports indicated that children with ASD had lower levels of PA and participated in a narrower range of activities than the TD children (Bandini et al, 2013). Further, Ketcheson et al (2018) found that preschoolers with ASD were less sedentary than TD children, while Pan et al (2011) found the opposite. However, there is encouraging evidence overall suggesting that people with ASD are at least capable of reaching the physical activity guidelines for TD individuals (Tyler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Further, Yang et al (2015) found increased motor performance and positive behaviors in young people with ASD as a result of PA, but the relationship between PA and cognition remained unclear. From a recent meta-analysis, fundamental motor skill training was positively correlated with PA and MVPA and negatively correlated with sedentary behavior in TD preschoolers (Engel et al, 2018), but the review by Ketcheson et al (2018) revealed no relationship between PA and motor skills in preschoolers with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…These support strategies should be used in combination with traditional protocol components including a 1-week monitoring period, providing written instructions, a monitoring log, and providing a self-addressed stamped return envelope. These methods were recently utilized with a younger sample of children with ASD with a 95% adherence rate ( 11 , 34 ). This suggests utility of these supports in younger samples.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, other studies have suggested that youths with ASD do not demonstrate PA deficits relative to their same-age peers. For example, Ketcheson et al [21] revealed that youths with ASD aged 2-5 years spent significantly more time in accelerometer-measured MVPA compared with youths without ASD. Pan and Frey [22] investigated PA patterns in youths with ASD aged 10-19 years and observed no differences in overall PA or MVPA regarding day-of-week and time-of-day variability according to participants' school level.…”
Section: Introductionmentioning
confidence: 99%
“…However, current evidence indicates that among youths with ASD, subjectively measured total screen time (e.g., TV viewing, video-gaming, and device use) ranged from 86 to 430 min/day (average 231 min/day), and objectively measured total sedentary time ranged from 312 to 789 min/day (average 514 min/day) [18]. Despite the substantial variations in estimates of screen time, few studies have revealed that youths with ASD spend more time engaging in sedentary activity than do TD youths [26][27][28], although this finding has not been consistently observed across all age groups [29] and varies based on method of data collection (e.g., survey [26,29] or accelerometry [21,27,28]). Chonchaiya et al [26] found that youths with ASD had significantly more screen time than TD youths (4.6 vs. 2.6 h/day) and fewer complied with screen time recommendations of less than 2 h/day (6% vs. 44%) compared with their TD counterparts.…”
Section: Introductionmentioning
confidence: 99%